Three deoxyribonucleic acid-dependent adenosine triphosphatases from Bacillus subtilis. - Mazza, G (1981)
We have isolated from Bacillus subtilis three deoxyribonucleic acid (DNA)-dependent adenosine triphosphatases (ATPases) (gamma-phosphohydrolases). The enzymes were extensively purified, and their physicochemical and functional properties were determined. The three enzymes (ATPases I, II, and III) were shown to be different by several criteria. ATPases II and III showed an absolute requirement for single-stranded DNA as a cofactor, whereas ATPase I had some residual activity also with double-stranded DNA. They required Mg2+ and had a pH optimum of 6.5 to 7. Only adenosine 5'-triphosphate and deoxyadenosine 5'-triphosphate were hydrolyzed. The molecular weights of ATPases I, II, and III were 108,000, 115,000, and 148,000, respectively. Km values for adenosine 5'-triphosphate and DNA were also evaluated and shown to be different for each enzyme. All three enzymes formed physical complexes with single-stranded DNA. We present evidence that ATPases I and II might migrate along DNA during adenosine 5'-triphosphate hydrolysis. On the other hand, this effect was not observed with ATPase III, which exhibited the highest affinity for single-stranded DNA.